Economic Evaluation of Selective Neonatal Bacillus Calmette-Guérin Vaccination of High-risk Infants in Ireland. Issue 8 (August 2018) - Teljeur, Conor; Moran, Patrick S.; Harrington, Patricia; Butler, Karina; Corcoran, Brenda; O'Donnell, Joan; Usher, Cara; O'Flanagan, Darina; Connolly, Kevin; Ryan, Máirín
Abstract : Background: In Western Europe, currently only Ireland and Portugal continue to provide universal neonatal bacillus Calmette-Guérin (BCG) vaccination programs, despite not being considered as high tuberculosis (TB) incidence countries. Other European countries only vaccinate infants considered at high risk of contracting TB. We evaluated the cost-effectiveness of selective BCG vaccination compared with strategies of universal and no vaccination. Methods: An economic model was used to simulate a cohort from birth to life expectancy, taking the perspective of the publicly funded healthcare system. BCG protection was modeled to last 15 years. International vaccine efficacy data were combined with Irish epidemiologic and cost data. The model took into account long-term sequelae associated with TB meningitis and severe adverse reactions relating to the BCG vaccine. A fully probabilistic model was used to incorporate uncertainty across all parameters. Results: At [Euro sign]139, 557 per quality-adjusted life year, selective vaccination was not cost-effective relative to a program of no vaccination. The incremental cost-effectiveness of universal vaccination was [Euro sign]2.55 million per quality-adjusted life year relative to selective vaccination. There was substantial uncertainty regarding the effectiveness of BCG vaccination. The cost-effectiveness of selective vaccination could be substantially improved by reducing the cost of administering the vaccine. Conclusions: In the absence of changes to other aspects of TB control, a switch to selective vaccination will result in increased cases of childhood TB. Although not considered cost-effective, selective vaccination may be preferable to no vaccination until other changes to TB control may be implemented to reduce the risk of TB in children. Abstract : Supplemental Digital Content is available in the text.